News Report: A Blended Extensive Reading and Intensive Reading Activity - Dung Thi Thanh Do (Journal of Development Research, 2017)
Reading plays an important role in widening knowledge and learning languages, but it is also a challenge. Although Vietnamese learners often get higher marks in English reading tests in comparison to other skills, students low motivation to read and their lack of general background knowledge are obvious. This presentation introduces News Report, a blended Extensive Reading - Intensive Reading activity. The process is consisted of four stages: choosing news, summarizing, making a glossary and presenting. The activity is designed with an aim of establishing the reading habit for learners to widen their knowledge and learn the target language simultaneously. As observed, it is unlikely to formulate the reading habit this way but it helps to guide students how to read effectively on their own. Participants will learn a multi-purpose reading activity and know how to apply it on their own or in their classroom.